Screening and assessment of performance and molecule quality attributes of industrial cell lines across different fed‐batch systems. (3rd November 2015) - Rouiller, Yolande; Bielser, Jean‐Marc; Brühlmann, David; Jordan, Martin; Broly, Hervé; Stettler, Matthieu
Abstract : The major challenge in the selection process of recombinant cell lines for the production of biologics is the choice, early in development, of a clonal cell line presenting a high productivity and optimal cell growth. Most importantly, the selected candidate needs to generate a product quality profile which is adequate with respect to safety and efficacy and which is preserved across cell culture scales. We developed a high‐throughput screening and selection strategy of recombinant cell lines, based on their productivity in shaking 96‐deepwell plates operated in fed‐batch mode, which enables the identification of cell lines maintaining their high productivity at larger scales. Twelve recombinant cell lines expressing the same antibody with different productivities were selected out of 470 clonal cell lines in 96‐deepwell plate fed‐batch culture. They were tested under the same conditions in 50 mL vented shake tubes, microscale and lab‐scale bioreactors in order to confirm the maintenance of their performance at larger scales. The use of a feeding protocol and culture conditions which are essentially the same across the different scales was essential to maintain productivity and product quality profiles across scales. Compared to currently used approaches, this strategy has the advantage of speeding up the selection process and increases the number of screened clones for getting high‐producing recombinant cell lines at manufacturing scale with the desired performance and quality. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 32:160–170, 2016